SP0076 Emerging genetics and molecular aspects of autoinflammatory bone disease. (23rd January 2014) - Ferguson, P.
Abstract : Autoinflammatory disorders of the bone are innate immune system disorders that result in chronic sterile inflammation in the bone. Chronic recurrent multifocal osteomyelitis (CRMO) is the most common autoinflammatory bone disorder in children and synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome is the most common autoinflammatory bone disease in adults. These disorders are often seen in conjunction with chronic inflammatory disorders of the skin (palmar plantar pustulosis and psoriasis vulgaris) and intestine (Crohn disease) suggesting shared pathophysiology. The genetic basis of several autoinflammatory bone diseases have been discovered by studying single gene disorders that have CRMO as a subphenotype. Mutations in LPIN2 cause Majeed syndrome, an autosomal recessive disorder which presents with CRMO, congenital dyserythropoietic anemia and neutrophilic dermatosis. Mutations in pstpip2 cause chronic multifocal osteomyelitis in an autosomal recessive murine model of the disease that is results in a phenotype and histology that is very similar to human CRMO, however, to date no PSTPIP2 mutations have been identified in humans with CRMO. Mutations in IL1RN which encodes the interleukin 1 receptor antagonist have been identified in infants with neonatal onset chronic sterile osteitis, sterile generalized pustulosis associated with systemic inflammation. This syndrome named DIRA (Deficiency of the Interleukin-1 Receptor Antagonist) unequivocally implicates the IL-1 pathway in the pathogenesis of sterile osteomyelitis. An update of the genetics and pathogenesis of the autoinflammatory syndromes will be presented. Disclosure of Interest: None Declared